Geographical characteristics of Silesia - Kosmala, Gerard (Wydawnictwo eBooki.com.pl, 2013)
This article contains basic geographical information about Silesia, useful as a starting point for further historical analysis. Silesia is a region of central Europe located within the borders of several nations. At different times in its history it has been part of Austria, the Czech Republic, Germany and Poland. The rough outline of the relief of Silesia was formed in the Paleozoic Era, finally reaching its ultimate form in the Cenozoic Era. The same holds true for both the Sudetes as well as the entire tectonic foreland, which was shaped by a glacier. Silesian land has always been rich in mineral resources such as building rocks, coal and copper, although only few of these can be found in abundance. The terrain’s shape results from the general structure of the hydrographical network which, with the exception of the eastern frontiers, is symmetrical, with the Odra river, flowing from the south-east to the north-west, as the axis of symmetry. Reservoirs have been built along many rivers for both energy-related and retention purposes. Due to the total absence of lakes, these reservoirs are the largest bodies of water in Silesia. The temperate, transitory climate with an annual average rainfall of 600–700 mm and average annual temperature of 8 °C results in conditions which are favourable for vegetation. Considering the abundance of fertile land one can easily understand why the agricultural scenery dominates the landscape. This, along with the development of industry at the base of the Sudetes and in the south-eastern part of Upper Silesia, is the reason for the relatively small amount of woodland areas. Silesia is an area which has been deeply transformed by human activity. The dominant landscape is culturally harmonious, with the exception of industrial districts, which often are the sight of more long-lasting changes that are often irreversible.
Keywords: regiony; Silesia